SEMINAR PUBLIKASI ILMIAH SEBAGAI STRATEGI PENINGKATAN KOMPETENSI AKADEMIK MAHASISWA DAN DOSEN DI PERGURUAN TINGGI - Repi Arianto; Didi Kosmanto; Wawan Herianto; Idi Warsah; Eka Apriani; Irwan Fathurrochman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of higher education in the globalization era requires strengthening research culture and scientific publication to improve academic quality. However, many students and lecturers still face challenges in scientific writing and publication, including limited academic writing skills, research methodology knowledge, reference management, and publication procedures. This study aims to analyze the role of scientific publication seminars in enhancing the academic competence of students and lecturers in higher education institutions. Using a qualitative approach with library research, data were collected from scientific journals, academic books, and relevant documents published between 2020 and 2025 and analyzed through descriptive content analysis. The findings indicate that scientific publication seminars improve research skills, scientific writing abilities, academic literacy, and understanding of publication ethics. In addition, these seminars contribute to increasing research motivation, publication productivity, and research culture within higher education institutions. Therefore, scientific publication seminars can serve as an effective strategy for strengthening academic competence and improving the quality of higher education.